2016
DOI: 10.1089/scd.2015.0315
|View full text |Cite
|
Sign up to set email alerts
|

Notch-Induced Expression of FZD7 Requires Noncanonical NOTCH3 Signaling in Human Breast Epithelial Cells

Abstract: The evolutionarily conserved Notch and Wnt signaling pathways have demonstrated roles in normal mammary gland development and in breast carcinogenesis. We previously reported that in human mammary gland, signaling through NOTCH3 alone regulates the commitment of the undifferentiated bipotential progenitors to the luminal cell fate, indicating that NOTCH3 may regulate the expression of unique genes apart from the other Notch receptors. In this study, we used gain of function and loss of function experiments and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 193 publications
(315 reference statements)
1
18
0
Order By: Relevance
“…These findings are corroborated by observations made in articular chondrocytes, demonstrating a reduction in FZD7 expression following pharmacological inhibition (AG490) of JAK2 [ 134 ]. More recently, the Notch signaling pathway, specifically NOTCH3 , was shown to regulate the expression of FZD7 in human mammary epithelial cells [ 135 ]. Further analysis revealed FZD7 to be expressed predominantly by luminal progenitor cells, which is hypothesised to regulate luminal cell differentiation through a NOTCH3-FZD7 signalling axis [ 135 ].…”
Section: Frizzledmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are corroborated by observations made in articular chondrocytes, demonstrating a reduction in FZD7 expression following pharmacological inhibition (AG490) of JAK2 [ 134 ]. More recently, the Notch signaling pathway, specifically NOTCH3 , was shown to regulate the expression of FZD7 in human mammary epithelial cells [ 135 ]. Further analysis revealed FZD7 to be expressed predominantly by luminal progenitor cells, which is hypothesised to regulate luminal cell differentiation through a NOTCH3-FZD7 signalling axis [ 135 ].…”
Section: Frizzledmentioning
confidence: 99%
“…More recently, the Notch signaling pathway, specifically NOTCH3 , was shown to regulate the expression of FZD7 in human mammary epithelial cells [ 135 ]. Further analysis revealed FZD7 to be expressed predominantly by luminal progenitor cells, which is hypothesised to regulate luminal cell differentiation through a NOTCH3-FZD7 signalling axis [ 135 ].…”
Section: Frizzledmentioning
confidence: 99%
“…We also showed that Notch3 negatively regulated EMT through Kibra-mediated Hippo/YAP and ERα signaling pathway in vitro 25 . Notch3 signaling inhibits EMT either by regulating target gene expression via interactions with the nuclear CBF1/RBP-Jκ/ S uppressor of Hairless/LAG-1 (CSL; RBP-Jκ in mice) transcriptional complex (e.g., ERα and Bmi1) or by regulating noncanonical expression of the Wnt signaling receptor frizzled7 (FZD7) 26 . These findings suggest that Notch3 signaling inhibits EMT in breast cancer cells by activating novel downstream genes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is tempting to speculate that SDC3 may associate with FZD7 during cell polarisation, not unlike SDC4 during the planar cell polarity (PCP) process in Xenopus, which also leads to activation of JNK 16 . Furthermore, in human breast epithelial cells FZD7 is induced by NOTCH signalling 52 , which is known to crosstalk with SDC3 during myogenesis 53 , thus further research is currently ongoing exploring the SDC3-NOTCH crosstalk in bone. Our findings are not explained by the lack of the SDC3 ectodomain in the light of Kim's and colleagues recent report of a suppressive effect of SDC1-4 ectodomains on osteoclastogenesis and of SDC1, 2 and 4 (but not SDC3) ectodomains on osteoclast mediated bone resorption 54 .…”
Section: Discussionmentioning
confidence: 99%